Master of Tourism and Hospitality Management - Kabale University (Kabale University, 2022)
The program blends the requisite specialist operational knowledge and skills, with advanced managerial competencies, in order to educate the new generation of tourism executives. It emphasizes the cross-cultural, moral, ethical, institutional and environmental issues in the management of tourism organizations, while covering all specialized business and operational skills.